Microscopic and Proteomic Analysis of Dissected Developing Barley Endosperm Layers Reveals the Starchy Endosperm as Prominent Storage Tissue for ER-Derived Hordeins Alongside the Accumulation of Barley Protein Disulfide Isomerase (HvPDIL1-1) - Roustan, Valentin; Roustan, Pierre-Jean; Weidinger, Marieluise; Reipert, Siegfried; Kapusi, Eszter; Shabrangy, Azita; Stoger, Eva; Weckwerth, Wolfram; Ibl, Verena (Frontiers in Plant Science, 2018)
Barley (Hordeum vulgare) is one of the major food sources for humans and forage sources for animal livestock. The average grain protein content (GPC) of barley ranges between 8% and 12%. Barley hordeins (i.e., prolamins) account for more than 50% of GPC in mature seeds and are important for both grain and flour quality. Barley endosperm is structured into three distinct cell layers: the starchy endosperm, which acts essentially as storage tissue for starch; the subaleurone, which is characterized by a high accumulation of seed storage proteins (SSPs); and the aleurone, which has a prominent role during seed germination. Prolamins accumulate in distinct, ER-derived protein bodies (PBs) and their trafficking route is spatio-temporally regulated. The protein disulfide isomerase (PDI) has been shown to be involved in PB formation. Here, we unravel the spatio-temporal proteome regulation in barley aleurone, subaleurone and starchy endosperm for the optimization of end-product quality in barley. We used laser microdissection (LMD) for subsequent nanoLC-MS/MS proteomic analyses in two experiments: in Experiment One, we investigated the proteomes of dissected barley endosperm layers at 12 days after pollination (DAP) and at ≥ 20 DAP. We found a set of 10 proteins that were present in all tissues at both time points. Among these proteins, the relative protein abundance of D-hordein, B3-hordein and HvPDIL1-1 significantly increased in starchy endosperm between 12 DAP and ≥ 20 DAP, identifying the starchy endosperm as putative major storage tissue. In Experiment Two, we specifically compared the starchy endosperm proteome at 6 DAP, 12 DAP and ≥ 20 DAP. Whereas the relative protein abundance of D-hordein and B3-hordein increased between 6 DAP and ≥ 20 DAP, HvPDIL1-1 increased between 6 DAP and 12 DAP, but remained constant at ≥ 20 DAP. Microscopic observations showed that these relative protein abundance alterations were accompanied by additional localization of hordeins at the periphery of starch granules and a partial re-localization of HvPDIL1-1 from PBs to the periphery of starch granules. Our data indicate a spatio-temporal regulation of hordeins and HvPDIL1-1. These results are discussed in relation to the putative role of HvPDIL1-1 in end-product quality in barley.